Phylogenetic relationships, systematics, and biology of the species of Amorbia Clemens (Lepidoptera: Tortricidae: Sparganothini) - Phillips-Rodríguez, Eugenie; Powell, Jerry A. (Zootaxa, 2007)
The systematics of the New World genus Amorbia Clemens, 1860, is revised. The genus ranges from Brazil through Central America, the Caribbean, Mexico, southeast and western United States and northeastern and southwestern Canada. Greatest species richness is found in middle elevations (500-1500 m) in Central and South America. Twenty-nine species are treated, 13 of which are described as new: A. monteverde (Puntarenas, Costa Rica), A. rhombobasis (Guanacaste, Costa Rica), A. cordobana (Veracruz, Mexico), A. cocori (Puntarenas, Costa Rica), A. cacao (Guanacaste, Costa Rica), A. catarina (Santa Catarina, Brazil), A. dominica (Dominica), A. knudsoni (Texas, U.S.A.), A. potosiana (Nuevo León, Mexico), A. chiapas (Chiapas, Mexico), A. santamaria (Quetzaltenango, Guatemala), A. curitiba (Paraná, Brazil), and A. stenovalvae (Tamaulipas, Mexico). Based on a phylogenetic analysis, five species previously included in Amorbia are excluded and assigned to incertae sedis: “Amorbia” depicta Walsingham, “Amorbia” elaeopetra Meyrick, “Amorbia” leptophracta (Meyrick), “Amorbia” rectilineana (Zeller), and “Amorbia” teratana (Zeller). One species, Amorbia revolutana (Zeller), is raised from synonymy, and three new synonymies are proposed: A. synneurana Barnes & Busck with A. cuneana (Walsingham); A. aequiflexa (Meyrick) with A. productana (Walker); and A. spylocriptis Meyrick with A. revolutana (Zeller). Eight informal species groups are proposed for purposes of discussing character states and their evolution: Curitiba (2 species), Productana (4 species), Humerosana (3 especies), Chiapas (2 species), Colubrana (8 species), Exsectana (1 species), Rectangularis (3 species), and Decerptana (6 species). A redescription of the genus is provided; all the species treated are illustrated (including male and female genitalia where known). Data on localities are listed, and maps showing species distribution are presented. Data on biology is provided for 12 species where inmatures stages are known; host plants for the species are listed. Additionally, a key to the species is provided based on male features.